Long-Term Survival and Tumor Recurrence in Patients with Superficial Esophageal Cancer after Complete Non-Curative Endoscopic Resection: A Single-Center Case Series - Ji Wan Lee; Charles J. Cho; Do Hoon Kim; Ji Yong Ahn; Jeong Hoon Lee; Kee Don Choi; Ho June Song; Sook Ryun Park; Hyun Joo Lee; Yong Hee Kim; Gin Hyug Lee; Hwoon-Yong Jung; et al. (Korean Society of Gastrointestinal Endoscopy, 2018)
Background/Aims To report the long-term survival and tumor recurrence outcomes in patients with superficial esophageal cancer (SEC) after complete non-curative endoscopic resection (ER). Methods We retrieved ER data for 24 patients with non-curatively resected SEC. Non-curative resection was defined as the presence of submucosal and/or lymphovascular invasion on ER pathology. Relevant clinical and tumor-specific parameters were reviewed. Results The mean age of the 24 study patients was 66.3±8.3 years. Ten patients were closely followed up without treatment, while 14 received additional treatment. During a mean follow-up of 59.0±33.2 months, the 3- and 5-year survival rates of all cases were 90.7% and 77.6%, respectively. The 5-year overall survival rates were 72.9% in the close observation group and 82.1% in the additional treatment group (p=0.958). The 5-year cumulative incidences of all cases of recurrence (25.0% vs. 43.3%, p=0.388), primary EC recurrence (10.0% vs. 16.4%, p=0.558), and metachronous EC recurrence (16.7% vs. 26.7%, p=0.667) were similar between the two groups. Conclusions Patients with non-curatively resected SEC showed good long-term survival outcomes. Given the similar oncologic outcomes, close observation may be an option with appropriate caution taken for patients who are medically unfit to receive additional therapy.